Wykonaj mnożenie i zredukuj wyrazy podobne.
a) (3×+2)(3×-2) + 2ײ=
b)(-5a-7)(3a+b)+a²-b=
c)(-8a-4)(-3a-9)-11a+a²=

A.Wykonaj mnożenie.
a)(x+1(y+z)
b)(a+3)(5-b)
c)(a-2b)(b-5)
B.Wykonaj mnożenie i zredukuj wyrazy podobne.
a)(x-4)(y+1)+xy
b)(1-p)(3p-4)-3p
c)(k-0,5l)(k+6)+k²
d)(c-1,5c)(12+c)-c²
C.Rozwiąż równanie.
a)2x(x+1)=2x²+4
b)(x-1)(x+2)=x²+5
c)(x+2)(x-1)=x²+5
d)(x-5)(x-10)=x(x+5)

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-10T21:40:39+01:00
A) (3×+2)(3×-2) + 2ײ=9x²-6x+6x-4+2x²=11x²-4
b)
(-5a-7)(3a+b)+a²-b=-15a²-5ab-21a-7b+a²-b=-14a²-8b-5ab-21a
c)
(-8a-4)(-3a-9)-11a+a²=24a²+72a+12a+36-11a+a²=25a²+73a-11




a)(x+1(y+z)=xy+xz+y+z
b)(a+3)(5-b)=5a-ab+15-3b
c)(a-2b)(b-5)=ab-5a-2b²+10b




a)(x-4)(y+1)+xy=xy+x-4y+4+xy=2xy+x-4y+4
b)(1-p)(3p-4)-3p=3p-4-3p²+4p-3p=-4-3p²+4p
c)(k-0,5l)(k+6)+k²=k²+6k-0,5kl-3l+k²=2k²+6k-0,5kl-3l
d)(c-1,5c)(12+c)-c²=12c+c²-18c-1,5c²-c²=-6c-1,5c












2009-12-10T21:41:53+01:00
A)= 9x²- 4 +2x² = 11 x² - 4
B)= - 15 a² - 5ab - 21a - 7b
C)= 24a²+ 72a + 12a + 36 = 24 a ² + 84a + 36

A)= xy + xz + y + z
B)= 5a - ab + 15 - 3b
C) = ab - 5a - 2b² + 10b

A)= xy + x - 4y - 4 + xy = 2xy + x - 4y - 4
B)= 3p - 4 - 3p² - 4p = -4 - 3p² - p
C)= k² + 6k - 0,5kl - 3
D)= 12c + c² - 18 c - 1,5 c²= -6c - 0,5 c²

A)2x²+ 2x=2x² + 4
2x = 4
x = 2
B)x² + 2x - x - 2 = x² + 5
x - 2 = 5
x = 7
C) x² + 2x - x - 2 = x² + 5
x - 2 = 5
x = 7
D) x²- 10 x - 5x + 50 = x² + 5x
- 15x - 5x = -50
20x = 50
x = 2,5